2021
DOI: 10.1371/journal.pone.0251033
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of a volunteer contact tracing program for COVID-19 in the United States: A qualitative focus group study

Abstract: Background Contact tracing is an important tool for suppressing COVID-19 but has been difficult to adapt to the conditions of a public health emergency. This study explored the experiences and perspectives of volunteer contact tracers in order to identify facilitators, challenges, and novel solutions for implementing COVID-19 contact tracing. Methods As part of a study to evaluate an emergently established volunteer contact tracing program for COVID-19 in New Haven, Connecticut, April-June 2020, we conducted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
37
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(43 citation statements)
references
References 43 publications
(63 reference statements)
4
37
0
2
Order By: Relevance
“…Bundling interventions to enhance impact is critical to solve what might be described as the pandemic's “Swiss cheese” problem, in which holes in the clinical and public health response arise at multiple levels, times, and locations to sustain the pandemic ( 42 ). Qualitative data collected in parallel with this project and published separately ( 41 ) supports this idea that even if contact tracing itself has gaps, it may still contribute to the overall public health response. Limited retrospective data from other settings also suggests that contact tracing may also contribute to improved cumulative outcomes ( 7 ), and this important question should be evaluated further in future prospective studies.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…Bundling interventions to enhance impact is critical to solve what might be described as the pandemic's “Swiss cheese” problem, in which holes in the clinical and public health response arise at multiple levels, times, and locations to sustain the pandemic ( 42 ). Qualitative data collected in parallel with this project and published separately ( 41 ) supports this idea that even if contact tracing itself has gaps, it may still contribute to the overall public health response. Limited retrospective data from other settings also suggests that contact tracing may also contribute to improved cumulative outcomes ( 7 ), and this important question should be evaluated further in future prospective studies.…”
Section: Discussionmentioning
confidence: 63%
“…In evaluating Adoption , we found volunteers to be a feasible, although not sustainable, solution to human resource shortages, given the high turnover among volunteers. We separately conducted focus groups with volunteers, described in detail elsewhere ( 41 ), who reported that burnout and transitions in academic roles and schedules likely contributed to decreased volunteer availability. Fortunately, the support of public health nurses bolstered capacity during surges and sustained the program.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the USA, several academic public health programmes and schools trained students as contact tracers in response to COVID-19 [18]. Community-based partnerships between universities and local health departments were established to compensate for workforce shortages [19][20][21]. These programmes were mostly volunteer-based [19,20,22,23], and students received academic credit and work experience in return [20,22].…”
Section: Discussionmentioning
confidence: 99%
“…The ability to quickly expand quality services to meet demand has emerged as a problem in need of innovative solutions that will be crucial in the current, but also possible future, pandemics. Different models have been employed to address this need, from the use of digital technology to recruitment of furloughed staff, health sciences students and volunteer led services in the US and elsewhere [39][40][41][42][43][44][45].…”
Section: Discussionmentioning
confidence: 99%